SOSIALISASI PENGEMBANGAN UMKM MELALUI PENGAJUAN PEMBIAYAAN BANK SYARIAH DI DESA SUKAMUKTI - Abdullah, Saqyllah Zahra; Rahmawati, Rafika; Isfandayani, Isfandayani; Mardiah, Siti; Isnandar, Fajri Ryan (LPPM Universitas Islam 45, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role as economic drivers in Indonesia, proven to be able to survive even in conditions of economic crisis. However, the MSME sector still faces major problems related to capital, especially in obtaining credit from banks with high interest rates and material collateral requirements that are difficult to meet. The development of various Islamic banking provides an opportunity to meet the needs of MSMEs, with a profit-sharing system that is different from conventional banking. This community service aims to provide understanding and increase the literacy of MSME actors regarding financing opportunities through Islamic banks. The service method applies socialization in the development of MSMEs by applying for financing at Islamic banks in Sukamukti Village. The results of the service show that MSME players can take advantage of the potential of Islamic banking to develop their business, increase better understanding of Islamic financing mechanisms, MSME players can overcome capital challenges and encourage economic growth.